Determinants of Low Birth Weight in Indonesia - Oktriyanto, Oktriyanto; Rahardja, Mugia Bayu; FN, Desi Nury; Amrullah, Hilma; Pujihasvuty, Resti; PN, Margareth Maya (KEMAS: Jurnal Kesehatan Masyarakat, 2022)
Low birth weight (LBW) is one of the main factors influencing the development of chronic disease in adulthood in surviving or surviving infants. This study aims to determine the determinants of the incidence of LBW in toddlers (infants aged 0-5 years) in Indonesia. This study uses a data set from the 2017 Indonesian Demographic and Health Survey (IDHS). The dependent variable is the child’s LBW status, while the independent variable consists of 3 variable blocks, namely; distal, intermediate and proximal variables. The number of samples in this study was 14,372 people. Data analysis was done descriptively and inferentially. The results showed that, of the 14,262 samples analyzed, 7% showed LBW. The highest probability of LBW was associated with the type of birth of twins (AOR: 22,087; 95%CI: 18,344-26,194), the order of birth of the 4th child or more (AOR: 2,231; 95%CI: 1,887-2.598), experiencing pregnancy complications (AOR: 1.887; 95% CI: 1.543-2.134), number of ANC visits less than 4 times (AOR: 1.763; 95% CI: 1.411-2.202), low maternal education (AOR: 1.711; 95% CI: 1.344-2.143), no consumption of iron tablets during pregnancy (AOR: 1.316; 95% CI:1.109-1.623), and households with low wealth quintiles (AOR: 1.301; 95% CI: 1.197-1.324. Various aspects have been associated with LBW which is expected to contribute on elaborating health and family policies and promoting better living conditions for mothers and children in Indonesia.